MEMILIH PASANGAN BAGI ANAK PEREMPUAN: KAJIAN FIQIH & HAM - Masthuriyah Sa’dan (IAIN Manado, 2016)
In Islamic jurisprudence (fiqh), the right to choose a partner for a woman is set by families. This then becomes the spotlight of many circles who argue that fiqh is discriminatory against women. Muslim men have the right to decide with whom to marry. In contrary, Muslim women do not have such a right. Women right is taken over by parents in the name of Islamic law. In the World Conference on Population and Women in Cairo-Egypt in 1994, however, women were proclaimed to have their own reproductive rights that must be protected and maintained. One form of the demands of the reproductive rights is the right of women to determine their own life partner. This paper wants to examine the right to choose a husband for women from the perspective of Islamic law and international law on human rights. Keywords: the right to choose, women, Islamic law, human rights.